THE IMPACT OF FUNCTION TRANSFER OF RICE LAND ON LOCAL RICE FOOD SECURITY IN NORTH SUMATRA: DAMPAK ALIH FUNGSI LAHAN SAWAH TERHADAP KETAHANAN PANGAN BERAS LOKAL DI PROVINSI SUMATERA UTARA - Harahap, Rahmaniah (UPMI Proceeding Series, 2023)
Rice is the main staple food of the Indonesian people. The need for rice from year to year continues to increase because of the increase in population and this need must be met. Food shortages affect malnutrition, health, and at the same time reduce the quality of human resources. Therefore, the government always strives to have and maintain food security, especially rice. However, along with these efforts in their operations, a vital problem faced at this time is the conversion of paddy fields. Alinh function of paddy fields from year to year continues to increase. If this situation continues, there is concern that it could threaten rice food security. The worst thing is that the land that has been converted cannot be returned to paddy fields as before. On the other hand, the production of new paddy fields is very small, constrained by high costs and a long time. In this regard, in this paper we wish to study the potential and conversion of paddy fields, production and demand for rice, constraints and strategies for having and maintaining rice food security. Based on the studies conducted, it can be concluded that the conversion of paddy fields is difficult to stop, efforts to maintain or maintain rice food security in the future will be increasingly difficult, the synergy of the components between the standard area of paddy fields, the application of technology packages to increase production and control population is still not stable . Therefore it is very necessary to have permanent rice fields, regulations to protect paddy fields, and a synergy model needs to be created between the area of paddy fields, the application of technology packages and the population so that food security is maintained.